Unraveling the Roles of Macrophages in Vascularized Composite Allotransplantation - Hui-Yun Cheng; Madonna Rica Anggelia; Cheng-Hung Lin (Biomedicines)
The phenotypic heterogeneity and functional diversity of macrophages have been increasingly appreciated, particularly regarding their roles as innate immune cells in shaping transplantation outcomes. However, their functions in vascularized composite allotransplantation (VCA) remain underexplored. In this review, we first describe the development of macrophages and the heterogeneity of macrophage differentiation, then present current insights into macrophages’ involvement across key stages of VCA, including ischemia–reperfusion injury at the peri-transplantation stage, and the outcomes following transplantation, including acute rejection, chronic rejection, and development of transplantation tolerance. The existing evidence supports that macrophages significantly influence both short- and long-term VCA graft survival. The presence of vascularized bone marrow within some VCA grafts further suggests the involvement of donor bone marrow-derived macrophage population and adds another layer of complexity to immune dynamics. Collectively, current understanding highlights the macrophage as a promising target for therapeutic intervention and warrants continued investigation into their diverse functions and potential for improving VCA outcomes.